Emociones en las personas privadas de la libertad de la Reclusión de Mujeres de Manizales (2020)
This research work aims to know the emotions of people deprived of liberty in the Manizales Women's Prison and where unionized and convicted women, who are referred from different regions of the country, have been taken as a population sample. Individual semi-structured interviews were conducted identifying the emotions of women for being deprived of liberty, of their support network, of their affective relationships, in the same way certain variables that appear in each life experience are evident.